Iron complexes of pharmaceutical interest: Antianemics - Cakić Milorad D.; Nikolić Goran S. (Hemijska Industrija, 2003)
Preparations based on different compounds of bi- and trivalent iron are curently used for the prevention and therapy of sideropenic anemia in human and veterinary medicine. The application of preparations based on dextran started about 1950. Up to now, synthesis and production of preparations were performed with the purpose of improving pharmacological performance by using dextran oligosaccharides with different weight - average molar masses and their oxidized and hydrogenated derivatives. Synthesis of polynuclear iron(lll) complexs with other oligosaccharides (inulin and pullulan) and their derivatives was developed, with potential or valid pharmacological activity for sideropenic anemia treatment.A Review of iron(lll) complexes with different oligosaccharides, their physico-chemical characterization pharmaco-biological performance, global structure, further research and possible applications of then complexes, are presented in this paper.